SYSTEMATIC VIOLATION BY A WORKER OF HIS LABOUR DUTIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes disciplinary responsibility and systematic violation of labour duties, application of disciplinary sanction as termination of labour contract. The purpose of the article is to investigate termination of labour contract at initiative of employer in connection with a systematic violation by a worker of his labour duties.